INTRODUCTION OF ARTIFICIAL INTELLIGENCE INTO ECONOMICS AND FINANCE, PRACTICE OF USE IN THE MODERN WORLD (Web of Discoveries: Journal of Analysis and Inventions, 2023)
In the article, the author outlines the degree of influence of artificial intelligence on the economy and business, and also examines its opportunities and problems.